2022
DOI: 10.3856/vol50-issue2-fulltext-2840
|View full text |Cite
|
Sign up to set email alerts
|

Development of enriched Artemia and Moina in larviculture of fish and crustaceans: a review

Abstract: Inconsistencies in the nutritional values of live food such as Artemia and Moina are well-known issues. The enrichment of live food is necessary to obtain the optimum nutrients needed for the growth, survival, and immune competence of fish and crustaceans' larvae. The enhanced growth and survival of fish and crustaceans' larvae are vital to continuous aquaculture production. However, enriched live food could be species-specific as various aquatic larval species may respond differently to the enrichment diets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Artemia was formerly categorized as a micro-crustacea for marine and fresh water. Hence, this zooplankton was low in HUFA so it is more suitable for feeding to freshwater fish [32]. From the previous study showed that new Artemia cyst were suitable food that might improve the growth and survival [33].…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Artemia was formerly categorized as a micro-crustacea for marine and fresh water. Hence, this zooplankton was low in HUFA so it is more suitable for feeding to freshwater fish [32]. From the previous study showed that new Artemia cyst were suitable food that might improve the growth and survival [33].…”
Section: Figurementioning
confidence: 96%
“…Live food was needed for early life stages of aquatic animal. By enrichment, it can increase the additional positive impacts on larval development and survival rate of larvae [32]. According to [37] Acipenser gueldenstaedtii larvae fed with Artemia enriched with lipid enrichment had improved growth in terms of growth performance of larvae.…”
Section: Specific Growth Rate (%)mentioning
confidence: 99%
“…Naturally, the Great Salt Lake in the USA was the first available natural habitat for the Artemia . However, because of their increasing demand for marine fish and crustacean larviculture [ 2 ], many inland salt lakes have emerged, such as in Bohai Bay, China, southern Siberia, Kazakhstan, and seasonal solar saltworks in the Mekong Delta, Vietnam. With the help of the European Union budget through the WorldFish organization, new efforts emerged for the potential sustainable production of Artemia in the area at Cox’s Bazar District, located in the southeast coastal zone of Bangladesh, through their available solar salt farm technology [ 3 ].…”
Section: Introductionmentioning
confidence: 99%